PENERAPAN ENVIRONMENTAL, SOCIAL, DAN GOVERNANCE (ESG) TERHADAP KINERJA PERUSAHAAN: SEBUAH TINJAUAN LITERATUR - Agisti, Chika Almalia; Widyaningsih, Aristanti; Rozali, Rozmita Dewi Yuniarti (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2025)
The purpose of this study is to investigate the implementation of Environmental, Social, and Governance (ESG) practices on corporate performance using a systematic literature review approach. The urgency of this research stems from the growing global emphasis on sustainability and the inconsistent findings of previous studies regarding the impact of ESG implementation on corporate performance. This study addresses the gap by providing a comprehensive review that encompasses various contexts and geographical backgrounds. A qualitative methodology is adopted, conducting an extensive review of studies from both developed and developing countries. The articles were selected based on specific inclusion and exclusion criteria from databases such as Scopus and Google Scholar. The literature review indicates that most studies find ESG implementation can enhance corporate performance. However, some studies report that ESG implementation may reduce performance, while others find no significant effect. These variations are influenced by geographical context (developed and developing countries) and the presence of moderating variables such as Governance mechanisms, sustainability strategies, and stakeholder engagement, which affect the strength and direction of ESGs impact on performance. Furthermore, the studies generally identify Governance as the most influential dimension, followed by environmental and social factors. This study offers valuable insights for companies, policymakers, and investors to understand better how strategic ESG integration can enhance corporate performance.